Triple Revolution Theory: An Innovative Marxist Framework Guiding the Direction of World Socialist Revolution in the Twenty-First Century (World Marxist Review, 2026)
Entering the New Era, General Secretary and President Xi Jinping has explicitly called for the need to "vigorously advance the spirit of carrying the revolution through to its completion." This important proposition is not merely a call of political will; rather, it constitutes a contemporary expression of Marxism's principle of thoroughness, revealing the fundamental driving force of Chinese-style modernization in the new era. It requires the comprehensive advancement of revolution and self-revolution across the political, economic, social, and cultural domains, the firm consolidation of the "Four Confidences", and the deepening of the "Two Integrations"—that is, integrating the basic principles of Marxism with China's concrete realities and with China's fine traditional culture. It is precisely within this intellectual context that Professor Cheng Enfu of the Chinese Academy of Social Sciences has proposed a systematically innovative theoretical framework—the Theory of the Triple Revolution. He argues that revolution constitutes the essential attribute of Marxism and operates on three fundamental levels: first, the Revolutionary Seizure of Power, which overthrows the old system and establishes a new political authority; second, the Reform Revolution, which continuously improves and develops the socialist system through self-revolution; and third, the Transitional Revolution, which realizes the historical transformation from the primary stage of socialism toward the comprehensive emancipation of humanity. These three revolutions are internally interconnected and progressively advanced, forming the systematicity, continuity, and thoroughness of Marxist revolutionary theory. Taking Professor Cheng Enfu's work "China's 'Triple Revolution Theory' and Marxist Analysis"¹, as its core text, this article examines the theoretical value and global significance of the Theory of the Triple Revolution within Xi Jinping Thought on Socialism with Chinese Characteristics for a New Era, from the three dimensions of philosophy, history, and civilization, thereby elucidating its internal logic and civilizational orientation as a form of Innovative Marxism.